Edukacja włączająca – wyzwanie dla kompetencji pedagogów specjalnych - Chrzanowska, Iwona (Studia Edukacyjne, 2018)
To prevent the marginalisation of young people, it is vital to have inclusive and fair education systems. Ensuring effective equal access to quality inclusive education for all learners, including those of migrant origins, those from disadvantaged socio-economic backgrounds, those with special needs and those with disabilities – in line with the Convention on the Rights of Persons with Disabilities – is indispensable for achieving more cohesive societies. Support educational staff and the students with special educational needs is important for success of inclusive education. These tasks can be carried out by teachers, special pedagogues. However, this requires changes in higher education programs in the field of special pedagogy. Inclusive education should be a compulsory education module. The question is what content the module should contain.